Modelagem de nicho ecológico das espécies de Phlebotominae e sua relação com a distribuição da leishmaniose tegumentar americana em região endêmica do Sudeste do Brasil - Meneguzzi, Viviane Coutinho (2016)
Cutaneous leishmaniasis (CL) is caused by a protozoan of the genus Leishmania and is transmitted by sand flies. The State of Espírito Santo (ES), an endemic area in the Southeast of Brazil, has shown considerably high prevalence in recent decades,allowing the expansion of the disease to unaffected areas. Computer tools, such as ecologic niche modelling (ENM), are useful for predicting potential disease risk. In this study, ENM was applied to species of sand flies and CL cases in ES to identify the principal vector and risk areas of the disease, aiming to understand the early origin and expansion of this disease. Sand flies were collected in 466 rural localities between 1997 and 2013 in the three hours after dusk using a combination of activeand passive capture. Insects were identified to the species level, and the localities were georeferenced. All medical records of autochthonous cases of CL attended at the University Hospital Cassiano Antonio de Moraes (HUCAM) between 1978 and 2013 were evaluated.